Aspects Concerning Corporate Governance in the Danube Region Countries - Hagiu, Alina; Bărbulescu, Marinela; Bâldan, Cristina (Journal of Danubian Studies and Research, 2024)
This study provides a comprehensive analysis of corporate governance practices across countries in the Danube region. Corporate governance frameworks vary significantly within this region due to diverse economic, legal, and cultural influences. The analysis examines the implementation of key corporate governance principles, including transparency and disclosure, board accountability, and shareholder rights. Countries like Austria and Germany adhere to a dual-board system, separating management and oversight roles, while others, such as Bulgaria and Romania, primarily employ a unitary board structure. The findings underscore progress made in aligning with international governance standards, driven by integration into the European Union and global economic pressures. Challenges persist, including corruption risks, political interference, and uneven enforcement of regulations, particularly in countries undergoing economic transition. The study highlights the ongoing need for reforms to enhance corporate governance effectiveness, promote investor confidence, and sustain economic development in the Danube region.